Factor analysis, reliability and validity of a Pashto version of Hamilton rating scale for depression - Irfan, Muhammad; Sethi, Mifrah Rauf (Journal of the Pakistan Medical Association, 2023)
Objectives: To translate and validate the Hamilton Rating Scale (HAM-D) for Depression in Pashto language. Method: The cross-sectional study was conducted at a tertiary care teaching hospital in Peshawar, Pakistan, from June to November 2021, and comprised patients of either gender diagnosed with depressive illness. The Hamilton Rating Scale for Depression was translated from English to Pashto by 3 bilingual experts using forward-backward method. The version was tested on the participants using exploratory and confirmatory factor analysis, Cronbach alpha reliability and construct validity of the scale. Data was analysed using SPSS 25 and AMOS 26. Results: Of the 507 patients with mean age 34.56+12.58 years, 317(62.5%) were females, 379(74.8%) were married and 308(60.7%) were uneducated. Factor analysis of HAM-D (Pashto) showed to be a four factor model and Bartlett’s test showed significant results indicating that the items was inter-correlated. Regarding construct validity, the factor loading through Item Total Correlation scores revealed highly satisfactory correlation coefficients. Cronbach’s alpha reliability of the Pashto version was 0.843, and confirmatory factor analysis indicated a good fit model (0.904) with root mean square error of approximation value 0.075. The scale showed 312(61.5%) participants were severely depressed. Married, uneducated patients and those with higher birth order were significantly severely depressed (p=0.000). Conclusion: The Pashto version of Hamilton Rating Scale for Depression was found to be a reliable instrument to measure depression and can be used in clinical settings. Key Words: Depression, Factor analysis, Psychometrics.